Computer-aided assessment of aviation pilots attention: Design of an integrated test and its empirical validation - Rosario Cannavò; Daniela Conti; Alessandro Di Nuovo (Applied Computing and Informatics, 2016)
Attention has a key role in the flight performance of the aviation pilot, therefore it is among human factors commonly used in the evaluation of candidate pilots. In this context, our work aims to define a single integrated instrument able to measure all the distinctive attention factors and to assist the assessment and the training of aviation pilots. In this paper, we present a battery of seven computerized tests, encompassing classical and innovative solutions inspired by the literature in the field, for the integrated measurement of the attention factors of aviation pilots. The computer software is validated by means of an experimental trial with 50 experienced aviation pilots and 50 untrained people as controls. Statistical analyzes confirm that the instrument can effectively classify aviation pilots, and identify a subset of distinctive attention factors that could be used for monitoring their duty.